HUMAN RESOURCES COMPETENCIES ENHANCEMENT USING INDIVIDUAL DEVELOPMENT PLAN (IDP) - Alifya Risya Putri (Jurnal Scientia, 2023)
Micro, Small and Medium Enterprises (MSMEs) is one of Indonesia's economic pillars. This research aims to help one of the MSMEs in the automotive sector in Indonesia, Garasi 64, to develop its human resource competence by making an individual development plan (IDP). The problem faced by the business is the dependence of the business operation on the owner which hinders the development of the business. This study used qualitative methods and coaching. The research is expected to help Garasi 64 to develop its human resource competencies.